Estudio de pertinencia para el diseño de la carrera de gestión de la calidad organizacional y productividad en la ESPAM MFL - Cedeño Alcívar, María Lorena (2022)
The objective of the research was the relevance criteria for the design of the Organizational Quality and Productivity Management degree program at ESPAM MFL. The study was developed in three stages: 1) analysis of the pertinence aspects; 2) identification of the main problems and tensions of the national and local reality; and 3) guidelines for the creation of the career. The study was mainly of a social and bibliographic nature. We worked with a sample of 164 high school students from local high schools. There was also the participation of 50 quality informants; representatives of the following sectors: public, private, civil society, academia and agriculture (10 for each sector). Family recommendations, peer opinion and social diversity were identified as the least influential aspects, while the most influential were exchanges, scholarships, anticipated income and costs. The 20 problems and tensions (4 per sector) that limit organizational quality and productivity were identified. Aspects for the creation of the career were outlined, based on the professional profile, seven minimum requirements, 38 training subjects and 10 final considerations. It is concluded that the evaluation of the pertinence criterion does determine the demands and needs for the design of the Organizational Quality and Productivity Management career; which allows the acceptance of the idea to be defended in the research.